A qualitative exploration of the lived experiences and perceived impact of a supportive-expressive group therapy on men living with gastrointestinal cancer. Issue 1 (11th January 2023) - Martopullo, Celestina; Oberoi, Devesh V.; Carlson, Linda E.; Bultz, Barry D.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Background: This study seeks to understand the functioning of a gastrointestinal (GI) men-only Supportive-Expressive Group Therapy (SEGT) program over time by exploring (1) men's lived experiences with group process and (2) perceived group impact relevant to supportive/expressive goals. Methods: A convenience sample of patients with GI cancer attending an ongoing, men-only GI cancer SEGT was interviewed at 3 and 6 months from enrollment. A qualitative study design with mixed inductive and framework thematic analysis was used. Open-ended, semistructured interviews directed the exploration of group experiences over time. SEGT goals framed the inquiry toward exploring the perceived impact of the group. Results: Twenty-three men were interviewed at 3 months and 13 men at 6 months of intervention. Men pointed to an overall global satisfaction with group process and subjects discussed. The SEGT model provided a sex sensitive, safe, and mutually supportive outlet for expressing and normalizing participants' feelings and emotions. Three central themes emerged relevant to group experiences: (1) the role of social comparison, (2) the role of supportive-expressive exchanges, and (3) the role of the group format, composition, and facilitation. Feeling heard and validated accelerated a sense of belonging and facilitated emotional disclosure. SEGT contributed to re-evaluation of life values/goals, mitigation of existential anxiety, and mood improvement. Conclusions: Group participants perceived the SEGT as effective in addressing and mitigating emotional and existential concerns. Perceived benefits were consistent with SEGT goals. The findings offer groundwork for developing men-centered cancer support groups that foster emotional exploration and expressive disclosure through validation and acceptance.